Modern information technologies in the civil process of foreign states and the Republic of Belarus: comparative legal analysis - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2024)
A comparative legal study is conducted on the topic of modern information technologies use in the civil process of foreign states and the Republic of Belarus in such areas as informing interested parties and the public about the procedure for resolving disputes, information support for the activities of courts, organising paperwork and resolving other issues, organisational issues, filing claims (other statements) in courts, distributing cases between judges, notifying participants in legal proceedings, judicial proof, etc. As a result, it was concluded that in terms of the level and depth of implementation of modern information technologies, domestic civil legal proceedings are in no way inferior to its foreign counterparts, although there is a certain potential for its improvement in this direction.